PERAN NEGARA TERHADAP PERLINDUNGAN HUKUM NARAPIDANA AKIBAT PANDEMI COVID-19 DI LEMBAGA PEMASYARAKATAN - Rabith Madah Khulaili Harsya; Anis Kurahmawati; Abdul Fatakh (UIN Siber Syekh Nurjati Cirebon, 2023)
Covid-19 has been declared a pandemic by the World Health Organization (WHO). Apart from causing a health emergency, the presence of this virus also has implications for several sectors such as finance which stem from an unstable economy. Based on this, the role of the state is needed to guarantee its prevention and handling. Indonesia as a constitutional state must guarantee certainty and protection by temporarily suspending coaching as a form of protection for convicts. Philosophically, the issuance of a circular letter from the director general of correctional institutions has considered the situation where cases of the spread of the Covid-19 outbreak are increasing day by day, so that the director general of correctional institutions acts as responsible for the situation in correctional institutions and continues to coordinate with the minister of law and human rights. (as the oversight of the penitentiary).This type of research is library research (library research), in the sense that all data sources come from written materials in the form of books, documents, magazines and texts that are related to the topic of discussion through a review of various literature related to research which includes primary, secondary data. , dantertier. The data collected, read.The results of this study, namely the results of this study are to explain and explain the role and efforts of the state in handling the pandemic as a form of manifestation of the purpose of the presence of the state, namely to protect the entire Indonesian nation.Â Keywords: The Role of the State, Legal Protection, and Guidance.